Quels sens pour les savoirs scolaires en démocratie ? Approches, lectures, défis - Camille Roelens (Recherches en Éducation)
The article proposes to deal with the question of the meaning of school knowledge in a democracy. We identify two privileged reflexive paths allowing us to progress towards the horizon of a more assured intelligibility in this domain – the epistemology of school knowledge and the political philosophy of education. We attempt a dialogue with the first from an anchorage in the second. The first part of our development is dedicat-ed to the respective contributions of Brigitte Frelat-Kahn, Marie-Claude Blais, Marcel Gauchet, Dominique Ottavi and finally Pierre Statius. Thus, we reconstruct an important moment of reflection on school issues in contemporary French democracy. The second part of our development identifies three major inspirations – Deweyian, Bachelardian and Tocquevillian – for thinking about our topic. We thus show, in dialogue with Michel Fabre's work, how the no-tion of problematicity of the democratic world can be a valuable guide to address two socially and politically rele-vant questions for thinking about school knowledge in a democracy: the individualist question and the liberal question.